2017
DOI: 10.1134/s0012496617050052
|View full text |Cite
|
Sign up to set email alerts
|

The structure of cnidosacs in nudibranch mollusc Aeolidia papillosa (Linnaeus, 1761) and presumable mechanism of nematocysts release

Abstract: The structure of cnidosacs in nudibranch mollusc Aeolidida papillosa (Linnaeus, 1761) before and after the discharging of kleptocnidae has been studied. In the apical zone of the cnidosac, the basal laminae of epidermis and gastrodermis are interrupted, and the muscle layers of the cnidosac and the epidermis are absent. We suggest the formation of a temporary channel during the discharging of the cnidosac. Through this channel, nematocysts move from the cnidosac to the cnidopore, which forms on the top of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The process of nematocysts extrusion from cnidosac remains poorly understood. While it is widely accepted that cnidosac discharging relates tomuscular contraction controlled by the nervous system (Greenwood & Mariscal, 1984; Goodheart & Bely, 2017; Vorobyeva et al, 2017) and our data also support this viewpoint (Figures 3, 10–13), there is no strict consensus on how kleptocnides are released from cnidophages into the seawater. Several authors suggested that cnidophages located close to cnidopore area may detach from basal laminae and be expulsed through a temporary cnidosac exit (Kälker & Schmekel, 1976; Greenwood & Mariscal, 1984; Martin et al, 2009).…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…The process of nematocysts extrusion from cnidosac remains poorly understood. While it is widely accepted that cnidosac discharging relates tomuscular contraction controlled by the nervous system (Greenwood & Mariscal, 1984; Goodheart & Bely, 2017; Vorobyeva et al, 2017) and our data also support this viewpoint (Figures 3, 10–13), there is no strict consensus on how kleptocnides are released from cnidophages into the seawater. Several authors suggested that cnidophages located close to cnidopore area may detach from basal laminae and be expulsed through a temporary cnidosac exit (Kälker & Schmekel, 1976; Greenwood & Mariscal, 1984; Martin et al, 2009).…”
Section: Discussionsupporting
confidence: 50%
“… Aeolidia papillosa , schematic drawing of the structure of the cnidosac, longitudinal section (modified from Vorobyeva et al, 2017). *, cnidopore; bl, basal lamina; ci, cilia; cmc, circular muscular layer of cnidosac; cmb, circular muscular layer of body; cnph, cnidophages; dg, digestive gland; ep, epidermis; he, haemocoel; ic, interstitial cell; lmb, longitudinal muscular layer of body; lmc, longitudinal muscular layer of cnidosac; lu, lumen; mv, microvilli; nc, nematocyst; nu, nucleus; sph, sphincter; va, vacuoles with chitinous spindles…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations